2021
DOI: 10.1155/2021/8810620
|View full text |Cite
|
Sign up to set email alerts
|

Association of Helicobacter pylori Infection and Host Cytokine Gene Polymorphism with Gastric Cancer

Abstract: The global cancer burden of new cases of various types rose with millions of death in 2018. Based on the data extracted by GLOBOCAN 2018, gastric cancer (GC) is the third leading cause of mortality related to cancer across the globe. Carcinogenic or oncogenic infections associated with Helicobacter pylori (Hp) are regarded as one of the essential risk factors for GC development. It contributes to the increased production of cytokines that cause inflammation prior to their growth in the host cells. Hp infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 115 publications
0
19
0
Order By: Relevance
“…Studies have shown that the level of PG I can reflect the secretory function of gastric glands to a certain extent, and its level is positively correlated with the maximum secretion of gastric acid but negatively correlated with the degree of gastric body inflammation and atrophy[ 17 ]. An increase in the level of PG II suggests an inflammatory response in the gastric mucosa, while a decrease in the level of PG I suggests atrophy of the gastric corpus[ 13 ]. When the gastric mucosa atrophies and develops severe injury, the number of gastric glands and fundic glands will decrease or be replaced by pyloric glands, and the pyloric glands lack gastric chief cells and cervical mucous cells, which will lead to a decreases in the level of PG I and the ratio of PG I/II[ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that the level of PG I can reflect the secretory function of gastric glands to a certain extent, and its level is positively correlated with the maximum secretion of gastric acid but negatively correlated with the degree of gastric body inflammation and atrophy[ 17 ]. An increase in the level of PG II suggests an inflammatory response in the gastric mucosa, while a decrease in the level of PG I suggests atrophy of the gastric corpus[ 13 ]. When the gastric mucosa atrophies and develops severe injury, the number of gastric glands and fundic glands will decrease or be replaced by pyloric glands, and the pyloric glands lack gastric chief cells and cervical mucous cells, which will lead to a decreases in the level of PG I and the ratio of PG I/II[ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cytokines produced by tumor cells or the tumor stroma can stimulate the survival, proliferation, and metastasis of cancer cells. These factors were demonstrated to be potential biomarkers for various cancers[ 13 - 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the initial stage of the colonization of H. pylori in the stomach, OMPs expressed on the bacterial surface are important as virulence factors and can bind to gastric epithelial cells [59]. The H. pylori genome has nearly 60 genes encoding the OMPs [60].…”
Section: Bacterial Virulence Factorsmentioning
confidence: 99%
“…Toll-like receptors (TLRs) belong to the large family of pattern recognition receptors (PRRs) and are important in the innate immunity of the host [90]. Among the 10 types of TLRs identified in humans [91], TLR2 and TLR4 on the gastric epithelial and immune cells are both associated with recognition of LPS composing the cell wall of H. pylori, acting as a primary defense against H. pylori [60,92]. However, it seems that TLRs, including these two molecules can play opposite roles, either promotion or suppression of H. pylori infection as innate immunity [90].…”
Section: Host Genetic Factorsmentioning
confidence: 99%
See 1 more Smart Citation